Social reference managers: scientific information in the 2.0 environment - Alonso-Arévalo, Julio (Anuario ThinkEPI, 2010)
In a few years we have evolved from bibliographic reference managers that only worked offline to management systems on the Web as a research tool. They make it easy to share, add and tag references. They support scientific discovery through the networks that are created between researchers´ personal bibliographies on related topics.
Keywords: Social reference managers; Web 2.0; Social tagging; Folksonomies; Information discovery.